THE LYSIS OF CELL WALLS OF GROUP A STREPTOCOCCI BY STREPTOMYCES ALBUS ENZYME TREATED WITH DIISOPROPYL FLUOROPHOSPHATE : CHARACTERISTICS OF THE LYTIC REACTION AND THE SOLUBLE CELL WALL FRAGMENTS - Schmidt, Willard C. (The Rockefeller University Press, 1965)
Diisopropyl fluorophosphate (DFP) effectively inhibited proteolytic activity in preparations of partially purified Streptomyces albus enzyme used to lyse cell walls of Group A streptococci. Lysis of non-trypsinized Group A cell walls with DFP-treated S. albus enzyme released a soluble protein fraction containing antigenic type-specific M protein, a carbohydrate fraction consisting of Group A and a small amount of A-variant polysaccharides, and a dialyzable fraction. The similarities of the products of DFP-treated S. albus enzyme lysis of streptococcal cell walls to those released by phage muralytic enzyme furnish additional evidence of the close relationship of these wall lysins. In view of small differences in electrophoretic mobility, immunodiffusion, and chemical composition, it is suggested that Group A streptococcal cell wall polysaccharide dissolved by DFP-S. albus enzyme consists of a spectrum of molecules having the same immunological determinants but differing in content of conjugated mucopeptide.